Giving Guava to Increase HB Levels in Anemic Pregnant Women at PMB Dince Safrina Pekanbaru - Octa Dwienda Rictica; Rita Afni (Journal of Midwifery and Nursing, 2021)
Pregnancy is a normal, natural process that begins with the growth and development of an intrauterine fetus and starts from conception to delivery. (Dewi, 2011). Hemodilution occurs from 10 weeks of gestation and peaks at 32-36 weeks of gestation. If the hemoglobin is before about 11 g%, the occurrence of hemodilution will result in physiological anemia and Hb will be 9.5 to 10 g%. Based on the report of the Pekanbaru City Health Office (2012), the number of pregnant women suffering from mild-moderate anemia in Pekanbaru City in 2011 was 1105 people and in 2012 there were 703 people. This research aims to determine the effectiveness of giving guava in increasing HB levels in pregnant women with anemia at PMB Dince Safrina Pekanbaru. This type of research is quasi experimental (quasi-experimental) with a one group pretest posttest approach. Sampling in this study using non random sampling technique with purposive sampling. The population in this study were all anemia pregnant women at PMB Dince Syafrina in November 2020. The analyzes used were univariate and bivariate. The results showed that there was an effect of giving Fe tablet and guava juice therapy to the increase in Hb levels of anemia in pregnant women. It is hoped that the special medical personnel for the Independent Practice of Midwife Dince Syafrina, SST, can formulate ways to treat anemia in pregnant women, namely not only providing therapy with iron tablets, but can combine it with 100 gr of guava per day and consumed 2 times a day. The results showed that there was an effect of giving Fe tablet and guava juice therapy to the increase in Hb levels of anemia in pregnant women. It is hoped that the special medical personnel for the Independent Practice of Midwife Dince Syafrina, SST, can formulate ways to treat anemia in pregnant women, namely not only providing therapy with iron tablets, but can combine it with 100 gr of guava per day and consumed 2 times a day. The results showed that there was an effect of giving Fe tablet and guava juice therapy to the increase in Hb levels of anemia in pregnant women. It is hoped that the special medical personnel for the Independent Practice of Midwife Dince Syafrina, SST, can formulate ways to treat anemia in pregnant women, namely not only providing therapy with iron tablets, but can combine it with 100 gr of guava per day and consumed 2 times a day.